Identifikasi Tumbuhan Pakan dalam Feses Kerbau (Bubalus bubalis Linnaeus) di Desa Penyangga Kawasan Taman Nasional Way Kambas: Identification of Forage Plants in Buffalo (Bubalus bubalis Linnaeus) Faecal at Buffer Village of Way Kambas National Park - Zulfa, Farrah; Dorly; Ariyanti, Nunik Sri (Departemen Biologi, Institut Pertanian Bogor, 2025)
The elephant in Way Kambas National Park (TNWK) is living side by side with the buffalos at the grazing area of TNWK’s buffer village. Considering that, the elephant may compete for food when the buffalo enters the conservation area. Data on the diversity of forage plant species is needed in managing buffalos livestock. This study aimed to identify the forage plants from undigested plant fragments in buffalo feces samples from TNWK’s buffer village. Samples were taken from 10 individuals of buffalo in savanna and palm oil plantation. Analysis of the plant composition was carried out by making microscopic whole mount paradermal sections of undigested plant fragments in the feces. Identification refers to epidermal characteristics that are matched with databases and references. The results showed that there were 21 types of epidermal cells which were dominated from Poaceae characterized by Gramineous stomata. The plants fragments found in almost all of the fecal samples were Hymenachne (Poaceae) and Fimbristylis (Cyperaceae). About 9 of the 21 species of plants consumed by buffalo in the buffer village are also foraged by elephants.